2023
DOI: 10.32996/ijllt.2023.6.3.17
|View full text |Cite
|
Sign up to set email alerts
|

Errors in Writing Among Female Students at the Tertiary Level in Saudi Arabia

Abstract: Writing is regarded as the most challenging skill to acquire when learning a foreign language. Extensive research into students' writing abilities is one method for understanding the challenges they face when writing. This study aims to investigate the most frequent English writing errors made by Saudi female university students at the tertiary level. The study's population comprised forty female college students. They had 45 minutes to write paragraphs on a variety of subjects. The participants in this study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 2 publications
0
0
0
Order By: Relevance
“…Spelling errors may be improved after giving students feedback (Nair & Hui, 2018). Nisa et al (2023) and Alzamil (2020) recommended adding more exercises focused on spelling and punctuation to the course outline.…”
Section: Implications and Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Spelling errors may be improved after giving students feedback (Nair & Hui, 2018). Nisa et al (2023) and Alzamil (2020) recommended adding more exercises focused on spelling and punctuation to the course outline.…”
Section: Implications and Recommendationsmentioning
confidence: 99%
“…Previous studies have shown that EFL learners face many difficulties and constantly make errors in mechanics (Shanorra et al, 2021) due to a lack of understanding of mechanics (Abbas & Herdi, 2018). Arabic-speaking students, in particular, tend to make more mistakes in mechanics than non-Arabic-speaking students (Alhaisoni et al, 2015;Al-Sobhi et al, 2017;Nisa et al, 2023). These errors often manifest in spelling, capitalization, and comma usage.…”
mentioning
confidence: 99%